2009
DOI: 10.1007/s00253-009-1944-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrafine-grained titanium surfaces on adhesion of bacteria

Abstract: The influence of the ultrafine crystallinity of commercial purity grade 2 (as-received) titanium and titanium modified by equal channel angular pressing (modified titanium) on bacterial attachment was studied. A topographic profile analysis of the surface of the modified titanium revealed a complex morphology of the surface. Its prominent micro- and nano-scale features were 100-200-nm-scale undulations with 10-15 microm spacing. The undulating surfaces were nano-smooth, with height variations not exceeding 5-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 27 publications
3
84
1
Order By: Relevance
“…roughness) on material surfaces are also crucial in cell and tissue responses to biomaterials. Indeed, surface roughness has shown to alter fibroblast proliferation on aluminiun, titanium and titanium alloys substrates [60][61][62] , and strongly influence bacterial attachment to nitinol, titanium and glass surfaces [63][64][65][66] . Overall, the three functionalization strategies displayed the same value of R a (~ 30 nm; Table 2), slightly increasing the original R a of control samples (~ 25 nm; Table 2).…”
Section: Physicochemical Characterization Of the Surfacesmentioning
confidence: 99%
“…roughness) on material surfaces are also crucial in cell and tissue responses to biomaterials. Indeed, surface roughness has shown to alter fibroblast proliferation on aluminiun, titanium and titanium alloys substrates [60][61][62] , and strongly influence bacterial attachment to nitinol, titanium and glass surfaces [63][64][65][66] . Overall, the three functionalization strategies displayed the same value of R a (~ 30 nm; Table 2), slightly increasing the original R a of control samples (~ 25 nm; Table 2).…”
Section: Physicochemical Characterization Of the Surfacesmentioning
confidence: 99%
“…In cases where the surface features were significantly smaller than the bacterial size, the contact area was reduced, resulting in a reduced extend of binding [15]. The level of extracellular polymeric substance (EPS) production and bacterial cell morphology have also been shown to be affected by the surface architecture [11,16,17]. Nano-patterning of gold surfaces has been demonstrated to enhance the localized attachment of P. fluorescens in the trenches of the surfaces compared to that obtained using native gold surfaces, with cells showing limited EPS production and reduced cell size compare to those attached onto non-nano-patterned surfaces [11].…”
Section: Introductionmentioning
confidence: 99%
“…11,[15][16][17] Recently, many studies have shown that changes in the surface topography at the nanometer level can interfere with mammalian cell as well as bacterial cell functions. 4,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Conventional biomaterials do not have nanoscale roughness. Nanoscale materials provide roughness and dimensions at the nano level which might influence bacteria behavior.…”
Section: Introductionmentioning
confidence: 99%